Screening of potential aerobic denitrifying bacteria for nitrate removal from water - Kirisan, A.; Gnanavelrajah, N.; Ratnayake, R.R. (National Science Foundation of Sri Lanka, 2022)
Nitrate pollution in groundwater is a common problem in areas where inorganic fertilizer is used to a large extent. This situation seriously affects communities that use ground water as their main source of drinking water and for many other purposes. Therefore, finding an efficient and cost effective system for the removal of nitrate from groundwater is an urgent necessity. The present study was aimed at identifying aerobic bacteria isolated from various soils and water sources and to test their potential for reducing nitrate in groundwater. The bacterial isolates (n = 128) were screened for nitrate reduction by various processes in nutrient broth and in mineral salt medium containing glucose and starch, using KNO3 as the nitrate substrate. Liberated gases during nitrate reduction were analyzed using gas chromatography. Out of 128 morphologically different isolates, two strains, namely Paracoccus sp. (A2) and Bacillus sp. (A19), were selected for further analysis on the basis of their performance for water treatment. The nitrate reduction percentages of A2 and A19 were within the range of 59.63-100% and 86.67-100%, respectively. Gas chromatography results indicated that these two strains liberated a higher percentage of N2 (68 - 90%) compared to N2 O (5-13%) and CO2 (traces), while reducing the amount of nitrate. These results confirmed that A2 and A19 have the potential to be used in bioremediation of nitrate contaminated groundwater.
Keywords: Bioremediation; Contamination; Groundwater; Isolates; Nitrate; Treatments